Literary Analysis Paragraphs: Advice & Practice - Bryla, Martyna Marika (My University, 2025)
This presentation was created for students of Literatura Norteamericana I at the University of Málaga. Its aim is to offer practical guidance on writing literary analysis paragraphs. Drawing on Paul Headrick’s approach (2014), it provides tips for structuring effective, coherent paragraphs while avoiding redundancy.
PIE22-104
Keywords: Literatura - Teoría y técnica; Literary analysis paragraphs; Topic sentence; Supporting sentences; Concluding sentence; Coherence